If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 7(-3x + -1) = -13 Reorder the terms: 13x + 7(-1 + -3x) = -13 13x + (-1 * 7 + -3x * 7) = -13 13x + (-7 + -21x) = -13 Reorder the terms: -7 + 13x + -21x = -13 Combine like terms: 13x + -21x = -8x -7 + -8x = -13 Solving -7 + -8x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -8x = -13 + 7 Combine like terms: -7 + 7 = 0 0 + -8x = -13 + 7 -8x = -13 + 7 Combine like terms: -13 + 7 = -6 -8x = -6 Divide each side by '-8'. x = 0.75 Simplifying x = 0.75
| 86=b-10 | | 0=2+15x-4.9x^2 | | 6z+11=9 | | 5n+5n=5n+10 | | 12y+24c=36 | | 3(x-3)=x-3(x+2) | | 12a+24y=36 | | 3x+9y=36 | | x=4+-4.5y | | 5-8v+4v=4v+5 | | 2x+9y=8 | | 0=-16t^2+80t+5 | | -4x-11[x+7]=-2[7x+4] | | 6a+12y=18 | | y=5*-2+3 | | w+7=5w-5 | | -14-4n=-6n-5n | | 2n-9=95 | | y=5*-1+3 | | y=5*0+3 | | x^2-8*x+5=0 | | y=5*1+3 | | .2(5-.3x)=.16x+.208 | | 3y+6c=9 | | 2y+4c=6 | | y=5*2+3 | | (x^2-2)(x^2+2)(x^2+4)(x+2)(x-2)=0 | | 15-9=k+18-29 | | -6a-[4-(3-2a)]=5a+6 | | N+20= | | 4ab*5xy= | | 4x+10=x-11 |